Expression of calretinin expression in odontogenic cysts and odontogenic tumors - Original research - Srinivasulu Pabbaraju; Kondala R Boddeda; Sravani Sankurathree; Ipseeta Menon; Narendra P Rai; Sai P Nagella (Wolters Kluwer Medknow Publications, 2024)
Aim: The present study was conducted for assessing variability in calretinin expression among odontogenic cysts as well as tumor cases. Materials and Methods: Fifteen cases were included in the present research consisting of cases like - dentigerous cyst, odontogenic keratocyst, apical radicular cyst along with tumors like ameloblastoma, ameloblastic carcinoma, adenomatoid odontogenic tumor. Calretinin antibody was used for immunohistochemical staining. The amount of expression of this calretinin was statistically analyzed with the help of Chi-square test where P < 0.05 was considered noteworthy statistically. Results: Most cases of ameloblastomas were highly positive for calretinin expression as compared to other cysts and tumors. Therefore, the correlation of this variation of expression of calretinin was statistically noteworthy (P = 0.00). Conclusion: In this study, we concluded that for ameloblastomas, calretinin can be a specific marker immunohistochemically and can help in identifying the amount of aggressive spread of various odontogenic tumors.